Therapeutic potential of calcitriol in cerebral ischemia/reperfusion injury: In vivo and in silico insights into TLR4 and FGFR2 pathways - Fahimeh Ramshini; Javad Amini Mahabadi; Reza Bayat; Sayyed Alireza Talaei; Zeinab Vahidinia; Hassan Hassani Bafrani (IBRO Neuroscience Reports, 2025)
Background: Cerebral ischemic injury remains a major cause of high mortality, with limited effective treatments available. Inflammatory responses play a critical role in the pathophysiology of cerebral ischemia/reperfusion (I/R) injury. Suppressing inflammation is a key strategy for mitigating cerebral I/R injury, making it a promising therapeutic target for stroke. Vitamin D supplementation has been revealed to exhibit anti-inflammatory and neuroprotective properties during I/R injury; however, the underlying protective mechanisms are not yet fully understood. This study aimed to investigate the effects of post-ischemic calcitriol treatment on ischemic stroke, focusing specifically on the TLR4/MyD88/NF-κB and FGFR2 signaling pathways Methods: Male Wistar rats were divided into three main groups: sham, I/R+ Vehicle, and I/R+ Calcitriol. An experimental I/R model was created by occluding the middle cerebral artery (MCA) for 1 h, followed by a 72-h reperfusion period. Calcitriol (1 μg/kg) was administered intraperitoneally for three consecutive days post-stroke. Neurological deficit scores and infarct size were evaluated 72 h after MCAO. Gene expression levels of TLR4, MyD88, NF-κB, and FGFR2 in the brain cortex were measured using RT-PCR. Additionally, histopathological changes in the cortex were examined with Nissl staining. A molecular docking analysis was performed to investigate the interactions of calcitriol with TLR4 and FGFR2, providing insights into their binding affinities and potential functional implications. Results: Our findings indicated that calcitriol treatment significantly enhanced neurological function (P < 0.05) and reduced infarct volume (P < 0.001) in cerebral I/R injury. Furthermore, calcitriol decreased the number of damaged neurons while markedly increasing the count of neurons with normal morphology (P < 0.001). Consistent with the results from molecular docking showing that calcitriol antagonizes TLR4 and FGFR2, RT-PCR analysis also revealed that calcitriol significantly suppressed the upregulation of TLR4 (P < 0.05), MyD88 (P < 0.01), NF-κB (P < 0.01), and FGFR2 (P < 0.001) mRNA expression levels. Conclusion: The results demonstrate that calcitriol treatment offers significant neuroprotective benefits following cerebral I/R injury. These protective effects may be mediated, at least in part, by the inhibition of inflammation through the TLR4/MyD88/NF-κB and FGFR2 signaling pathways. This study enhances our understanding of the molecular mechanisms involved in calcitriol's neuroprotective actions.